From one winning career to the next : transitioning public sector leadership and security expertise to the business bottom line - Quilter, J. David (Risk management portfolio., 2013)
In From One Winning Career to the Next, author J. David Quilter expertly guides the security professional through the corporate landscape. Having transitioned into the private sector from a long career in public service with the DEA, Quilter offers valuable perspective on the differences in culture and priorities between the public and private sectors, and how those differences can affect efforts in organizational security. Readers will benefit from the author's insights on researching and joining a new organization, exploring a business' structure and culture, and getting to know the executives and leaders within a business. Chapters contain practical advice on specific challenges (crisis management, assaultive behavior, threats to corporate assets, etc.), forming an effective team, and making a business case to gain executive support for a security agenda. This book is vital background for security professionals considering career changes. It will also aid those in established positions in their efforts to communicate, strategize, and implement security programs and goals within a business. Provides tips for all aspects of a career change, including narrowing the job search, preparing for an interview, presenting yourself in an interview, researching a company, and evaluating a position. Prepares security leaders for specific challenges they may face during the transition into a new positionIncludes easily adaptable, on-the-job lessons for a newly hired security leader.